Extending the Group Actor-Partner Interdependence Model: MSEM Applications. (April 2022) - Bonito, Joseph A.
The Group Actor-Partner Interdependence Model (GAPIM) conceptualizes group composition as a relational construct and provides methods for estimating the effects of compositional characteristics on outcomes of interest. This paper extends the GAPIM to a multilevel structural equation model framework, which expands the range of research questions the GAPIM might address, including those based on input-process-outcome models. Simulations, based on group size, number of groups, effect size, and compositional skewness, provide guidance for designing studies to maximize power to detect compositional effects. Discussion addresses composition in general, especially how "deep" characteristics become manifest and meaningful during interaction.